(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
Disclosure of the Statement of Value Added (DVA) is optional for credit unions and mandatory for publicly traded banks. This study aims to demonstrate possible values for the DVAs of the cooperatives Sicoob and Sicredi, which do not make such disclosure, and to compare with the statements of the financial institutions Banco do Brasil and Itaú, for the period from 2015 to 2018. The study used documentary procedures for collecting data on the statements of the institutions studied on their websites. By comparing the Value-Added Statements of each institution over the last four years, it was possible to identify that Sicredi cooperative led the segments of equity remuneration and third-party capital remuneration, Banco do Brasil the taxes, fees and contributions segment, while its competitor, Banco Itaú, accumulated the highest percentage of taxes to be recovered. In the personal segment, the Cooperative Sicoob stands out as being the institution that most pays its employees.